2004
DOI: 10.1002/jcp.20059
|View full text |Cite
|
Sign up to set email alerts
|

Plasmalemmal vacuolar H+‐ATPase is decreased in microvascular endothelial cells from a diabetic model

Abstract: Angiogenesis requires invasion of extracellular matrix (ECM) proteins by endothelial cells and occurs in hypoxic and acidic environments that are not conducive for cell growth and survival. We hypothesize that angiogenic cells must exhibit a unique system to regulate their cytosolic pH in order to cope with these harsh conditions. The plasmalemmal vacuolar type H(+)-ATPase (pmV-ATPase) is used by cells exhibiting an invasive phenotype. Because angiogenesis is impaired in diabetes, we hypothesized that pmV-ATPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 41 publications
0
8
1
1
Order By: Relevance
“…In addition to increased protease expression and activity, our data show that knockdown of VATPase a3 caused the decrease in cellular motility. Several reports indicated that V-ATPase in plasma membranes also colocalizes with actin at the leading edge of migrating cells, suggesting that V-ATPase is involved in dynamic actin remodeling (37,38). These data collectively indicate that V-ATPase a3 in plasma membranes possesses dual roles and thus contributes to the increase in cancer invasiveness.…”
Section: Discussionmentioning
confidence: 59%
“…In addition to increased protease expression and activity, our data show that knockdown of VATPase a3 caused the decrease in cellular motility. Several reports indicated that V-ATPase in plasma membranes also colocalizes with actin at the leading edge of migrating cells, suggesting that V-ATPase is involved in dynamic actin remodeling (37,38). These data collectively indicate that V-ATPase a3 in plasma membranes possesses dual roles and thus contributes to the increase in cancer invasiveness.…”
Section: Discussionmentioning
confidence: 59%
“…Endothelial cells adjacent to an induced wound display inducible and prominent plasma membrane v-ATPase localization and activity 10. Endothelial cells obtained from diabetic rat models, however, display significantly reduced cell surface v-ATPase activity and show a functional impairment in migratory behavior 40. These findings indicate that physiological and wound-repair processes likely require plasma membrane v-ATPase activity, possibly due to the effects on MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Normal microvascular endothelial cells have been shown to express plasma membrane V-ATPase, particularly at the leading edge of migrating cells [31,32]. Moreover, inhibition of V-ATPases with the specific inhibitor bafilomycin greatly reduced the invasiveness of these cells, suggesting that V-ATPases play a key role in angiogenesis.…”
Section: Functions In the Vas Deferens And Epididymusmentioning
confidence: 99%
“…It has recently been shown that microvascular endothelial cells from a diabetic rat model are deficient in plasma membrane V-ATPase [31,32]. Because angiogenesis is defective in diabetes and because V-ATPases have been implicated in an invasive phenotype, it has been suggested that the absence of plasma membrane V-ATPase activity in microvascular endothelial cells may contribute to defective angiogenesis in diabetes.…”
Section: Functions Of Plasma Membrane V-atpases In Human Diseasementioning
confidence: 99%